Hypertension in pediatric patients admitted to inpatient ward at King Abdulaziz Universty Hospital in Saudi Arabia: Prevalence, causes, and outcomes - Osama Safdar; Reham AlJehani; Mohammed Aljuhani; Hajar AlGhamdi; Arub Asiri; Oyoon AlGhofaily; Fatimah Hisan; Ghidah Altabsh (Journal of Family Medicine and Primary Care, 2020)
Background: The secondary hypertension (HTN) is the predominant form of HTN in pediatrics. Renal diseases and renovascular anomalies are the most commonly reported causes. In this study, we aimed to identify the prevalence, causes, and outcomes of secondary HTN in Saudi Arabia. Methods: A retrospective study was conducted among 3,640 pediatric patients aged between 0 and 18 years, admitted to the pediatric nephrology ward at King Abdulaziz University Hospital, Jeddah, Saudi Arabia. The study has been approved by the ethics review committee of King Abdulaziz University. Results: Prevalence of secondary HTN due to renal disease was (77.0%). Most of the cases were diagnosed with stage 5 renal disease (78.3%). Small kidney size was frequently diagnosed (n = 29, 11.9%), followed by large kidney size (n = 26, 10.7%). One third of the cases (n = 79, 32.4%) were under control, 49 (20.1%) lost follow-up, and 24 (10.1%) deceased. A total of 61 (33.1%) patients progressed to end-stage renal disease and patientswere managed by different types of treatments. Conclusion: The prevalence of secondary HTN due to renal disease is considered to be high in pediatric patients admitted to King Abdulaziz University. Several renal diseases in the renal system are associated with secondary HTN mostly attriubuted to renal malformation. In addition, renal affection, cerebral infarction, bleeding, left ventricular hypertrophy, and valvular lesion are the highest reported complications in our population. Follow-up with ECHO and brain CT is highly recommended in pediatric HTN. Future studies on a larger sample and vigorous follow-up are recommended.